Comparison of survival outcomes and effects of therapy between subtypes of high-grade endometrial cancer – a population-based study. (3rd July 2021) - Scharl, Sophia; Gerken, Michael; Sprötge, Tim; Kronberger, Karin; Scharl, Anton; Ignatov, Atanas; Ortmann, Olaf; Kölbl, Oliver; Klinkhammer-Schalke, Monika; Papathemelis, Thomas
Abstract: Background: Similarities in outcome between grade 3 endometrioid cancer and non-endometrioid histologies have been reported by a number of studies. Other reports, however, stated a significantly better prognosis for G3 endometrioid compared to type II histology. In this population-based study, we compared the outcome and treatment approaches of high-grade endometrial cancer patients with FIGO stages I–III depending on their histology. Material and methods: 284 high-grade endometrial cancer patients diagnosed between 1998 and 2015 were retrospectively analyzed. Overall survival (OS), recurrence-free survival (RFS), and recurrence rates were compared depending on histology. Results: Type I G3 patients had a statistically significant OS advantage over women suffering from type II carcinoma (HR 1.527, 95%-CI 1.024–2.276; p  = 0.038) and carcinosarcoma (HR 2.106, 95%-CI 1.270–3.493; p  = 0.004) in univariable and multivariable Cox-regression analysis. RFS in Type I G3 was significantly superior compared to patients with carcinosarcoma (HR 1.719, 95%-CI 1.018–2.901; p  = 0.043) and not significantly superior to type II patients (HR 1.368, 95%-CI 0.920–2.036; p  = 0.122). Cumulative recurrence rates were significantly higher in carcinosarcoma compared to type I G3 (HR 2.217, 95%-CI 1.096–4.485; p  = 0.027) in univariable analysis, but not after risk adjustment (HR of 1.472, 95%-CI 0.654–3.311; p  = 0.350). Conclusion: The prognosis of patients with type I G3 endometrial cancer patients seems to be significantly superior to patients with type II cancer and particularly carcinosarcoma. Systematic LND seemed to be beneficial in all of the three subtypes. The benefit of adjuvant treatment methods may differ between histologies.